Histopathological Evaluation of the Effects of Pistacia atlantica Extract on a Mouse Model of Diabetic Wound - Hadi Esmaeili Gouvarchin Ghaleh; Ebrahim Salimi Sabour; Majid Mirzaee Nadoushan; Bahman Jalali Kondori (Negah Institute for Scientific Communication, 2023)
Introduction: Type 2 diabetes is the most common type of diabetes characterized by insulin resistance and beta cell dysfunction. The speed of wound healing is very important in the healing process. Research shows that the use of natural products and traditional medicine methods in treating many diseases and wounds has spread worldwide. Therefore, the present study aims to investigate the histopathological effectiveness of Pistacia atlantica extract (Beneh) in improving the experimental model of diabetic wounds.  Methods: This study was conducted on 48 BALB/c mice. To induce type 2 diabetes, the animals received a high-fat diet for two weeks, and then a single dose of 30 mg/kg was injected intraperitoneally. The wound was created by an excisional wound splinting model and biopsy punch. Glucose level was measured with a glucometer, and insulin level was measured using an ELISA kit. Histopathological examination was also done using hematoxylin/eosin staining and Masson trichrome staining. Results: The macroscopic study showed that the wound size was reduced in both P. atlantica extract and silver sulfadiazine groups compared to the wound control group. The results of hematoxylin and eosin staining also showed a reduction in inflammation in the wound area in the treatment groups. The re-epithelialization occurred well in both treatment groups. However, its speed was higher in the P. atlantica-treated group than in the silver sulfadiazine group. Masson's trichrome staining results showed the collagen fibers in the P. atlantica group have a more regular arrangement than silver and wound control groups. The results of the serum analysis also showed that the gum extract of P. atlantica reduced the production of NO and MPO in the treatment groups compared to the control group. Conclusion: The results of our study showed that the use of P. atlantica extract topically in the diabetic wound area can improve the rate of closure and re-epithelialization in the diabetic wound by reducing inflammation.